A facile development of homemade substrate using 'quench free' glass-ceramic composite and printing microstrip patch antenna on it. (5th January 2018) - Abhilash, Pullanchiyodan; Roshni, Satheesh Babu; Mohanan, Pezholil; Surendran, Kuzhichalil P.
Abstract: The development of a non-conventional (NC) LTCC glass-ceramic composite using a unique 'quench free glass', and subsequent realization of a patch antenna on this substrate, are reported. This novel composition is comprised of Sr2 ZnTeO6 (SZT) and 5 wt% of ZBPT (10 mol% ZnO – 2 mol% B2 O3 – 8 mol% P2 O5 – 80 mol% TeO2 ) glass where the latter reaction mixture can be added directly to the ceramic, bypassing the high temperature melt quenching step. The average particle size distribution shows a more uniform and narrow distribution of powder prepared through non-conventional approach, compared to the conventional approach (C) where the quenched glass powder was added to the ceramic. The sintered tapes show εr values of 11.64 and 12.12 for both SZT + ZBPT (C) and SZT + ZBPT (NC) respectively. The breakdown strength of both sintered tapes comes > 1100 V/2 mil. The SZT + ZBPT (NC) tape show lower leakage current and better resistivity (5.3 × 10 8 Ω·cm) compared to SZT + ZBPT (C) (2.9 × 10 8 Ω·cm). In order to check the feasibility of developed LTCC tape as microwave substrates, a prototype of ceramic patch antenna operating at 2.5 GHz was designed and printed on sintered LTCC tapes of SZT + ZBPT (NC) and its radiation characteristics were analyzed and discussed. Graphical abstract: Highlights: A facile, energy efficient strategy was developed for LTCC substrate applications Sintered tapes of non-conventional approach show high resistivity (5.3 × 10 8 Ω·cm). The breakdown strength of sintered tapes comes > 1100 V/2 mil. A printed antenna operating at 2.5 GHz with a return loss of − 19 dB was fabricated.